RELIGIOSITY AND LONGITUDINAL CHANGE IN PSYCHOSOCIAL FUNCTIONING IN ADULT OFFSPRING OF DEPRESSED PARENTS AT HIGH RISK FOR MAJOR DEPRESSION. Issue 1 (29th May 2013) - Kasen, Stephanie; Wickramaratne, Priya; Gameroff, Marc J.
<x xml:space="preserve">Abstract</x> Background Recent findings suggest that beliefs about religious or spiritual importance or attending religious/spiritual services may protect high‐risk offspring against depression. This research has not extended to examining religiosity in relation to psychosocial functioning in high‐risk offspring. Methods Offspring selected for having a depressed parent and offspring of nondepressed parents were evaluated for lifetime major depressive disorder (MDD) in childhood and adolescence, and at 10‐year (T10) and 20‐year (T20) follow‐ups. Relations between self‐reported religiosity at T10 and longitudinal change in psychosocial function from T10 to T20 (assessed by clinical ratings on Global Assessment Scale [GAS]) were examined separately in 109 daughters and 76 sons by risk status. Results Lifetime MDD was diagnosed in 57.8% of daughters and 40.8% of sons by T20. Among daughters, only those with lifetime MDD showed improved psychosocial functioning in relation to higher level of service attendance at T10, their mean GAS score improving by 3.5 points (P = .018) over the next decade. For daughters with and without lifetime MDD, relations between higher levels of religiosity and improved psychosocial function were of greater magnitude in those with a depressed parent. Among sons, only those with lifetime MDD showed improved psychosocial function in relation to higher level of religious/spiritual importance, their mean GAS score improving by 4.6 points (P < .0001) over the next decade; that relation was of greater magnitude in sons with both lifetime MDD and a depressed parent. Conclusions Greater improvement in psychosocial functioning in relation to religious involvement in more vulnerable offspring supports religiosity as a resilience factor.